2020
DOI: 10.3390/ijms21041447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diet and Nutrition on Prostate Cancer

Abstract: The incidence of prostate cancer (PCa) displays widespread regional differences, probably owing to differences in dietary habits. Nutrients, including fat, protein, carbohydrates, vitamins (vitamin A, D, and E), and polyphenols, potentially affect PCa pathogenesis and progression, as previously reported using animal models; however, clinical studies have reported controversial results for almost all nutrients. The effects of these nutrients may be manifested through various mechanisms including inflammation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 143 publications
1
106
0
10
Order By: Relevance
“…Finally, accelerated prostate cancer progression has also been associated with inflammation caused by a high-fat diet in PTEN-deficient prostate cancer mouse models, suggesting that alterations to patient diet and/or exercise regimens may be especially beneficial for those with PTEN-deficient disease [ 394 , 395 , 396 ]. Although the clinical data available are still not clear on which nutrients may offer the most protection, switching to a ketogenic diet which encourages the body to burn fat may prove to be a beneficial approach [ 217 ].…”
Section: Pten and The Tumor Microenvironmentmentioning
confidence: 99%
“…Finally, accelerated prostate cancer progression has also been associated with inflammation caused by a high-fat diet in PTEN-deficient prostate cancer mouse models, suggesting that alterations to patient diet and/or exercise regimens may be especially beneficial for those with PTEN-deficient disease [ 394 , 395 , 396 ]. Although the clinical data available are still not clear on which nutrients may offer the most protection, switching to a ketogenic diet which encourages the body to burn fat may prove to be a beneficial approach [ 217 ].…”
Section: Pten and The Tumor Microenvironmentmentioning
confidence: 99%
“…Prostate cancer is the most diagnosed cancer in men after skin cancer and has the second highest cancer-related mortality [36]. Historically, it was widely believed that fat intake was both a risk factor for the development of prostate cancer and likely a contributor for worse outcomes [37]. In fact, animal model studies have provided proof for this claim; Ngo et al, among others, showed that immunodeficient mice, engrafted with a prostate cancer xenograft, had a slower tumor progression and a longer life span if fed a fat-restricted diet.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Diet can rapidly alter the composition of the microbiome [ 20 , 21 , 22 , 23 ]. A western diet high in meat products, providing nutrients such as choline and carnitine, can cause certain gut bacteria to produce trimethylamine (TMA).…”
Section: Introductionmentioning
confidence: 99%